Gains And Losses from an Open Line Program as Perceived by By-Passed Managers: A Case Study - Bird, Monroe M. (Academy of Management Journal, 1973)
The article presents the result of a survey on the attitude of lower level managers toward the open line program of the U.S. Air Force in Wiesbaden, Germany. The open line program was established to enable anyone in the organization to dial a widely advertised telephone number any time or night and have his message recorded and personally heard or read by the wing commander or his staff. A total of 94 lower level managers, between operatives and wing headquarters, who were subject to bypass by the open line program, were interviewed. The vast majority of respondents expressed resentment towards the program, only six of the respondents expressed favorable attitudes toward the program.